Exploration of Students' Epistemological Obstacles in Understanding the Concept of Variables and Expressions - Rosliana Siregar; Muhammad Daut Siagian; Tommy Tanu Wijaya (Didaktik Matematika, 2023)
Variables and expressions serve as bridges where students cross from arithmetic to algebra. Although variables and expressions are important concepts in middle school and high school mathematics, they are topics that many students find challenging, and many, in fact, do not develop a thorough understanding of these topics. This study aims to explore the epistemological obstacles students face in understanding and interpreting the concepts of variables and expressions. Based on these objectives, a qualitative research design with a phenomenological approach was chosen to achieve this research objective. The subjects in this study were 8th grade middle school students in the city of Medan, Indonesia. Tests and interviews were used to collect data. The data obtained were analyzed using an inductive approach. The data obtained are presented in narrative and graphical forms. Based on the research results obtained, six types of student errors in solving problems related to the concept of variables and expressions were identified. Overall, students' limitations in understanding and interpreting variables as something unknown is one of the triggers for epistemological obstacles. Teachers should give chances for pupils to debate and explain variables and expressions in the classroom to assist students gain a comprehensive knowledge of these mathematical tools.